Determinants of firm valuation: empirical evidence from Vietnam, Thailand and Malaysia - Nguyen, Quy (2019)
The purpose of this study is identifying which variables had significant impacts on value of firms and based on that, giving investors suggestions about what factors should be concerned when making investments. This research focuses on 5 determinants, including accounting rate of return, growth of EBITDA, working capital management, firm size and financial leverage, on firm valuation, using annual data of non-financial firms from three South East Asia countries, Vietnam, Thailand and Malaysia, from 2008 to 2018. These relationships are investigated using regression analysis. There are three main results extracted from this study. Firstly, only relationship between profitability and firm value is positive in all circumstances and that between firm size and firm value is negative and significant most of cases, while effects of other factors are uncleared and varied by countries and models, therefore, profitability and firm size should be concerned more when making investments than others. Secondly, among three countries, value of Malaysian firms is explained the best by our models, with the highest R2, and affected more by our variables, with higher coefficients than those of Vietnam and Thailand. It means that using our mentioned variables in choosing investments, investors can create more value investing in Malaysian firms. Finally, return on invested capital ROIC is the better proxy of profitability than return on equity ROE in explaining firm value because models using ROIC had higher R2 than those using ROE, thus, investors should focus more on ROIC. However, this study still consists some limitations: small sample size, huge number of non-listed firms, not detecting all types of relations and proxies for variables are probably inappropriate. Therefore, to receive better results, further studies should avoid these problems by increasing sample size, using other measurements and other forms of relations.